Pengaruh Implementasi Prinsip-Prinsip Good Corporate Governance dan Manajemen Risiko pada Kinerja Keuangan Koperasi Simpan Pinjam di Kecamatan Buleleng - Marsa Kusuma putra; Wayan Cipta (Universitas Pendidikan Ganesha, 2021)
This study aimed at examining the effect of good corporate governance (GCG) and risk management on financial performance in cooperatives in Buleleng district. This research employed a quantitative approach. The samples of 12 savings and loans cooperatives. The sample was selected using a purposive sampling method. Respondents in this study were 36 people. The data were collected through questionnaires. The data analysis technique used in this research was multiple linear regression analysis. The results showed Good Corporate Governance (GCG) and risk management simulated affect financial performance. (2) Good Corporate Governance (GCG) partially affects financial performance. (3) Risk Management partially affects financial performance.Keywords: Good Corporate Governance (GCG), risk management and financial performance